Effects of continuous cooling and isothermal cooling parameters on microstructure and mechanical properties of EH420 marine steel - Hui Liu; Zhiqiang Wu; Guili Xu; Junhong Yu; Daheng Xiao; Wenhao Zhou; Biao Deng; Xuhui Liu; Jun Hu (Journal of Materials Research and Technology)
This study aims to investigate the effects of continuous cooling after deformation at 900 °C and isothermal cooling after deformation at 830 °C on the microstructure and mechanical properties of EH420 steel, emphasizing ferrite structure evolution. As the continuous cooling rate increases from 0.3 °C/s to 50 °C/s at 900 °C, the fraction of ferrite and pearlite decreases, while the percentage of bainite and martensite increases. Correspondingly, the hardness increases from 180 HV5 to 323 HV5. Meanwhile, the ferrite undergoes a transformation from polygonal to an elongated morphology, and the average grain size decreases from 13.6 ± 6.3 μm to 3.7 ± 1.5 μm due to fast cooling, which limits grain growth. During the isothermal cooling process, the microstructure mainly consists of ferrite, pearlite, and a mixed structure of bainite and martensite. When the cooling rate increases from 0.3 °C/s to 3 °C/s at 830 °C, the average grain size of polygonal ferrite decreases from 8.7 ± 3.2 μm to 5.4 ± 3.5 μm, while the hardness increases from 199 HV5 to 233 HV5. The isothermal cooling process can result in equiaxed ferrite grains with a smaller size and promote the formation of pearlite and bainite with high dislocation density.